TINJAUAN KECERDASAN YUSUF BERDASARKAN KECERDASAN SPIRITUAL (SPIRITUAL INTELLIGENCE), KECERDASAN EMOSIONAL (EMOTIONAL INTELLIGENCE), KECERDASAN INTELEKTUAL (INTELLECTUAL INTELLEGENCE) DAN KETANGGUHAN (ADVERSITY QUOTIENT) - Purwanto, Agus (Sekolah Tinggi Teologi Kristus Alfa Omega, 2020)
One of the people chosen by God to prepare a country and its people in fulfilling His plan, that person was Joseph. Joseph as the maker of history and the link that connects the Book of Genesis to the Book of Exodus, was chosen by God to fulfill His plan, not by going through a smooth road, but there are many steep and abyss as a life experience to go through. The inclusion and guidance of God, made Joseph have something